Prevalence and patterns of cognitive impairment in acute coronary syndrome patients: A systematic review. (February 2020) - Zhao, Emma; Lowres, Nicole; Woolaston, Anna; Naismith, Sharon L; Gallagher, Robyn
Background: Minimising risk factors through secondary prevention behaviour is challenging for patients following an acute coronary syndrome. Cognitive impairment can potentially make these changes more difficult. However, cognitive impairment prevalence in acute coronary syndrome patients is poorly understood. Design: This study was based on a systematic review. Methods: A systematic review was conducted of PubMed, Medline, PsycINFO and Cochrane databases up to March 2019, to identify studies reporting the prevalence of cognitive impairment in acute coronary syndrome patients. Predefined inclusion criteria were specified, including use of a validated cognitive impairment screening tool. Studies were excluded if patients had diagnosed dementia or coronary artery bypass graft surgery. Strengthening The Reporting of Observational Studies in Epidemiology and Cochrane Risk of Bias tools were used to assess quality. Results: From 747 potential studies, nine were included. The total sample size was 6457 (range 53–2174), mean age range was 51.3–77.4 years, and range of proportions of males was 57–100%. Reported cognitive impairment prevalence rates varied substantially (9–85%) with no clear pattern over time. From the two studies which examined domains, verbal fluency, memory and language were affected the most. Meta-analysis could not be undertaken due to diverse screening tools ( n = 9), cut-off scores and screening timepoints. Conclusions: Cognitive impairment in acute coronary syndrome patients is currently poorly described, and likely affects a substantial number of acute coronary syndrome patients who remain undetected and have the potential to develop to dementia in the future. As domains are most affected, this could impact understanding and retention of health education. Research is needed to accurately determine the prevalence of cognitive impairment in acute coronary syndrome patients and create suitable standardised measures and thresholds.